Politik Identitas Islam Indonesia Kontemporer: Radikalisme Islam Versus Moderatisme Islam dalam Politik Elektoral Pilpres 2019 (Contemporary Indonesian Islamic Identity Politics: Islamic Radicalism Versus Islamic Moderatism in the 2019 Presidential Election Electoral Politics) - Rubaidi Rubaidi; Dwi Setianingsih (Institut Agama Islam Negeri (IAIN) Manado, 2021)
ABSTRACTThis article examines an important aspect that has not been widely studied in previous writings, namely the dimensions of the contestation of radical Islamic groups and moderate Islamic groups in the 2019 electoral political stage. The representation of radical Islam is represented by the GNPF-MUI which includes Islamic organizations such as FPI, FUI, Larkar Jihad and others. Meanwhile, moderate Islam is represented by Nahdlatul Ulama (NU), some Muhammadiyah and other moderate mass organizations. Behind the frenzy of